Employee Perceptions of Green HRM Practices: A Qualitative Study in Makassar’s Manufacturing Sector - Haeruddin, M. Ikhwan Maulana (Journal Management & Economics Review (JUMPER), 2025)
This qualitative study explores employee perceptions of Green Human Resource Management (Green HRM) practices within Makassar's manufacturing sector, employing interpretive phenomenology to understand lived experiences and attitudes toward environmental sustainability initiatives. Through semi-structured interviews with 23 employees from eight manufacturing companies, the research utilized reflexive thematic analysis to identify key patterns and meanings. Four primary themes emerged: limited awareness but growing curiosity about Green HRM practices, perceived benefits extending beyond environmental impact to include health improvements and career development, strong alignment between environmental initiatives and cultural-religious values, particularly Islamic stewardship principles, and significant implementation challenges, including inadequate infrastructure and communication gaps. The findings reveal that while employees demonstrate genuine interest in environmental sustainability, successful Green HRM implementation requires culturally sensitive approaches that integrate local values with comprehensive organizational support systems. The study contributes to limited qualitative research on Green HRM in developing countries, highlighting the importance of contextualizing environmental management practices within Indonesian cultural and religious frameworks. Results suggest that manufacturing organizations must develop holistic strategies combining environmental education, infrastructure investment, and continuous engagement mechanisms to effectively implement Green HRM practices.